ANALISIS PELAYANAN TENAGA KERJA RSUD MAJALAYA TERHADAP PENDAFTARAN ONLINE SEHINGGA TERJADI KECAKAPAN TEKNOLOGI BAGI LANSIA - Burhanudin, Raihan; Alistia, Resti Dwi; Khoerurizki, Rivana Dwi; Ginanjar, Sunandie Eko (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
The registration system is one of the hospital service strategies which is expected to help patient needs, shorten waiting times, increase patient satisfaction and service effectiveness. This research was conducted so that problems regarding online registration at the Majalaya Regional Hospital can be evaluated and be useful for the community, especially the elderly, so that they know more about the online registration method at the Majalaya Regional Hospital and with this online registration it can make it easier for the community, especially the elderly, to register. In the Employment Services method, in an effort to analyze employment services at Majalaya Hospital for online registration so that technological skills for the elderly occur, this uses a descriptive qualitative method. Descriptive qualitative data collection techniques use interview methods, field notes, photos, videotapes, personal documents, notes or memos and other official documents. The implementation of online registration at Majayala Regional Hospital can be said to be less effective for the elderly because many elderly people currently do not understand technological skills, for example having to register online via the JKN application.